Tight junction, mucin, and inflammasome‐related molecules are differentially expressed in eosinophilic, mixed, and neutrophilic experimental asthma in mice. Issue 2 (5th November 2018) - Tan, Hern‐Tze Tina; Hagner, Stefanie; Ruchti, Fiorella; Radzikowska, Urszula; Tan, Ge; Altunbulakli, Can; Eljaszewicz, Andrzej; Moniuszko, Marcin; Akdis, Mübeccel; Akdis, Cezmi A.; Garn, Holger; Sokolowska, Milena
Abstract: Background: Asthma is a chronic respiratory disease with marked clinical and pathophysiological heterogeneity. Specific pathways are thought to be involved in the pathomechanisms of different inflammatory phenotypes of asthma; however, direct in vivo comparison has not been performed. Methods: We developed mouse models representing three different phenotypes of allergic airway inflammation—eosinophilic, mixed, and neutrophilic asthma via different methods of house dust mite sensitization and challenge. Transcriptomic analysis of the lungs, followed by the RT‐PCR, western blot, and confocal microscopy, was performed. Primary human bronchial epithelial cells cultured in air‐liquid interface were used to study the mechanisms revealed in the in vivo models. Results: By whole‐genome transcriptome profiling of the lung, we found that airway tight junction (TJ), mucin, and inflammasome‐related genes are differentially expressed in these distinct phenotypes. Further analysis of proteins from these families revealed that Zo‐1 and Cldn18 were downregulated in all phenotypes, while increased Cldn4 expression was characteristic for neutrophilic airway inflammation. Mucins Clca1 (Gob5) and Muc5ac were upregulated in eosinophilic and even more in neutrophilic phenotype. Increased expression of inflammasome‐related molecules such as Nlrp3, Nlrc4, Casp‐1, and IL‐1β was characteristic for neutrophilic asthma. In addition, we showed that inflammasome/Th17/neutrophilic axis cytokine—IL‐1β—may transiently impair epithelial barrier function, while IL‐1β and IL‐17 increase mucin expressions in primary human bronchial epithelial cells. Conclusion: Our findings suggest that differential expression of TJ, mucin, and inflammasome‐related molecules in distinct inflammatory phenotypes of asthma may be linked to pathophysiology and might reflect the differences observed in the clinic. Abstract : Tight junction, mucin, and inflammasome‐related molecules are differentially expressed in the lungs in distinct inflammatory phenotypes of allergic airway inflammation (AAI): eosinophilic, mixed, and neutrophilic AAI. Zo‐1 and Claudin‐18 are downregulated, whereas Clca1 (Gob5) and Muc5ac are upregulated in all phenotypes. Claudin‐4, Nlrp3, Nlrc4, Casp‐1, and IL‐1β are upregulated in neutrophilic AAI. IL‐1β impairs epithelial barrier function and increases MUC5AC expression in differentiated primary human bronchial epithelial cells (HBECs). IL‐17 also increases MUC5AC expression in HBECs.